The Effectiveness Of Prenatal Yoga Movements To Improve The Sleep Quality Of Pregnant Women Tm Iii At Pmb Midwife Umroh Grogol Sukoharjo - Umi Hartatik, Pramita Sandy Ulya Imannura; Enyk Yunanto (Journal for Quality in Public Health, 2025)
Yoga also affects the hypothalamus to suppress the secretion of CRH which will affect the anterior lobe pituitary gland to suppress the release of the hormone ACTH so that the production of adrenal hormones and cortisol decreases and orders the anterior lobe pituitary gland to release the hormone endorpin. Yoga will inhibit the increase of sympathetic nerves so that the hormones that cause body dysregulation can be reduced in number. The parasympathetic nervous system signals to influence the release of catecholamines, resulting in a decrease in heart rate, breathing rhythm, blood pressure, muscle tension, metabolic rate and the production of hormones that cause anxiety or stress.To determine the effectiveness of prenatal yoga to improve the quality of sleep of pregnant women TM III.Pre-experimental design is one-group pretest- posttest design where one group of subjects and observations are made before and after treatment. The population in this study were all TM III pregnant women with sample criteria being pregnant women who had a gestational age of 28-40 weeks and without any complications during pregnancy as many as 20 people. Data analysis using univariate analysis, normality test, bivariate test with Wilcoxon.Normality test with Kolmogorov smirnov test showed p=0,000 so it is not normal. Statistical test results with Wilcoxon test showed that the value of p=0.000 (p<0.05) which showed that there was an effect of prenatal yoga on increasing. There is an effect of prenatal yoga movements on improving the quality of sleep of third trimester pregnant women.